Development of Problem-Based Student Worksheet on Environmental Change Material - Nadya Welli Astuti; Bernadetta Octavia (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to determine the feasibility and practicality of problem-based student worksheets on environmental change material. This research is a type of development research (research and development) with research procedures using the 4D Model which consists of the stages of define, design, develop, and disseminate. This research was conducted at SMA Negeri 1 Godean in Class XI semester II. This student worksheet contains environmental problems in Yogyakarta. Based on the results of the study, showed that problem-based student worksheet on environmental change material is suitable for use with a percentage of 71.25% by material experts and 82.1% by media experts. The assessment of the biology teacher as a practitioner expert obtained results with a percentage value of 82.91% with a very practical category to use and an assessment of students with a percentage of 76.82% with a category worth using. It can be concluded that problem-based student worksheets are feasible and practical to use in the implementation of learning biology of environmental change material.